2003
DOI: 10.3136/fstr.9.378
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and the Glucosides Inhibit Nitration of a Salivary Component 4-Hydroxyphenylacetic Acid Catalyzed by Salivary Polymorphonuclear Leukocytes

Abstract: Mixed whole human saliva contains 4-hydroxyphenylacetic acid (HPA), nitrite and polymorphonuclear leukocytes. Salivary leukocytes nitrated HPA to 4-hydroxy-3-nitrophenylacetic acid in the presence of nitrite, and phorbol myristate acetate stimulated the nitration. Quercetin and the glucosides, which are found in the oral cavity after ingestion of quercetin-rich foods, inhibited the leukocyte-dependent nitration. The inhibition by quercetin and the glucosides was in part due to the flavonol-dependent scavenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Salivary peroxidase bound to bacteria may be responsible for this as it has been reported that oral bacteria bind salivary peroxidase (8). In addition to salivary peroxidase, myeloperoxidase is also a probable candidate because the bacterial fraction may have been contaminated with salivary leukocytes (12). The contribution of peroxidases to the formation of NO 2 HPA was supported by the result that 1 mM KCN and 1 mM NaN 3 almost completely inhibited NO 2 HPA induced during incubation of the bacterial fraction (pH 5.3) for 30 min in the presence of 0.1 mM HPA, 2 mM glucose, 0.3 mM nitrite, and 0.2 μg of glucose oxidase per ml.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salivary peroxidase bound to bacteria may be responsible for this as it has been reported that oral bacteria bind salivary peroxidase (8). In addition to salivary peroxidase, myeloperoxidase is also a probable candidate because the bacterial fraction may have been contaminated with salivary leukocytes (12). The contribution of peroxidases to the formation of NO 2 HPA was supported by the result that 1 mM KCN and 1 mM NaN 3 almost completely inhibited NO 2 HPA induced during incubation of the bacterial fraction (pH 5.3) for 30 min in the presence of 0.1 mM HPA, 2 mM glucose, 0.3 mM nitrite, and 0.2 μg of glucose oxidase per ml.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, certain bacteria and leukocytes in the oral cavity can produce , which is then converted into hydrogen peroxide (H 2 O 2 ) (8–10). It has been reported that HPA can be nitrated, producing 4‐hydroxy‐3‐nitrophenylacetic acid (NO 2 HPA), by salivary peroxidase/H 2 O 2 /nitrite systems (11–13). Nitric oxide formed by the reduction of nitrite‐reducing bacteria may also contribute to HPA nitration, as NO is transformed to NO 2 and ONOO − (pKa = 6.8), both of which are nitrating reagents, by reacting with O 2 and , respectively (14).…”
mentioning
confidence: 99%
“…It has been reported that peroxidases can oxidize nitrite to nitrogen dioxide radicals, which can participate in the nitration of tyrosine and tyrosine residues in proteins ( ), by the following reactions: Here, compound I is a complex of peroxidase and atomic oxygen and compound II is the one-electron reductant of compound I . We have suggested that myeloperoxidase from salivary leukocytes and salivary peroxidase can also oxidize nitrite to nitrogen dioxide radicals ( , ). The nitration induced by nitrogen dioxide radicals can be inhibited by polyphenols ().…”
Section: Introductionmentioning
confidence: 99%
“…During polyphenol-dependent inhibition of nitration, polyphenols including quercetin are oxidized ( , ). It has been reported that a stable oxidation product of quercetin can be separated by HPLC and that the product gives 2,4,6-trihydroxyphenylglyoxylic acid and 3,4-dihydroxybenzoic acid when oxidized by a peroxidase/H 2 O 2 system ().…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation